Field‐based versus laboratory‐based estimates of muscle quality index in adolescents with and without Down syndrome. Issue 12 (23rd June 2022) - Melo, G. L. R.; Moraes, M. R.; Nascimento, E. F.; Boato, E. M.; Beal, F. L. R.; Stone, W.; da Cunha Nascimento, D.
Abstract: Background: Low muscle quality index (MQI) is a potential risk of developing functional impairments in older people. However, considering that individuals with Down syndrome (DS) present with a faster decline in biological aging, an investigation on MQI in individuals with DS is necessary. The aims of this present cross‐sectional study were to compare (1) MQI between adolescents with and without DS and (2) evaluate laboratory versus field‐based estimates of MQI. Methods: Fifty‐six adolescents were recruited and separated into two groups: DS ( n  = 30, 13 boys and 17 girls; age: 12.38 ± 3.07 years) and a control (non‐DS; n  = 26, 9 boys and 17 girls; age: 12.46 ± 2.88 years). Laboratory MQI was derived from the ratio of grip strength to arm muscle mass (in kg) measured by dual‐energy X‐ray absorptiometry (DXA). Field‐based MQI was quantified from the ratio of hand grip strength (HGS) to body mass index (BMI). For statistical analyses, a two‐way ANOVA was conducted for group comparisons, and a Pearson correlation was used to test the association between field MQI and laboratory MQI. Results: Adolescents with DS displayed lower field ( P  = 0.001), laboratory MQI estimates ( P  = 0.001) and HGS ( P  = 0.001) as compared non‐DS. Also, there was a strong correlation effect between field MQI and laboratory MQI estimates ( P  < 0.001, R  = 0.81). Conclusion: Adolescents with DS have lower field and laboratory MQI compared with adolescents without DS. Simpler field MQI might be used in daily clinical practice, with special attention to those with DS.